2015
DOI: 10.1179/1743284714y.0000000607
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of as aged Mg–3Sn–1Al and Mg–3Sn–2Zn–1Al alloy

Abstract: Effect of Zn on the microstructure, age hardening response and mechanical properties of Mg3Sn-1Al alloy which is immediately aged at 180uC after extrusion process (T5) was investigated. It was found that the Zn can refine the microstructure, remarkably improve the aging response with the peak hardness increases to 75 HV and the time to peak hardness reduces from y110 to y60 h, which is attributed to the solid solution hardening of Al, Zn and an amount of finer Mg 2 Sn precipitates. The as aged Mg-3Sn-2Zn-1Al a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Comparing the present work with other mechanical properties of the Mg-Sn-Zn alloys (Figure 11), this work successfully prepared the TZK alloy with higher plasticity while maintaining a relatively high strength. 1,10,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Figure 12 showed the tensile fracture morphology of TZK alloys under different deformation conditions. Obviously, the fracture mode of the DT-1 alloy was ductile fracture, as its fracture morphology was composed of deep and uniform dimples.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the present work with other mechanical properties of the Mg-Sn-Zn alloys (Figure 11), this work successfully prepared the TZK alloy with higher plasticity while maintaining a relatively high strength. 1,10,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Figure 12 showed the tensile fracture morphology of TZK alloys under different deformation conditions. Obviously, the fracture mode of the DT-1 alloy was ductile fracture, as its fracture morphology was composed of deep and uniform dimples.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…69 The SF values of the {0001}<11-20 > basal slips, {1-100}<11-20 > prismatic slips and {−1-122}<11−23 > pyramidal slips for TZK alloys with different deformation conditions were listed as Figure 13, and the results showed the basal and pyramidal slips of DT-1 alloy had higher SF values. It 1,10,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] was important that the higher the SF value of slips was prone to activate. That might be the reason for its good mechanical properties at room temperature.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, introducing Sn element into Mg alloys has been proposed to form the Mg 2 Sn strengthening phase with high-temperature resistance. Additionally, its melting point (778 • C) is much higher than that of the Mg 17 Al l2 phase (498 • C) in traditional AZ Mg alloys, and the hardness value is up to 119 HV [1,2]. Therefore, it could be concluded that the Mg 2 Sn phase is an excellent heat-resistant Mg alloy strengthening phase [3].…”
Section: Introductionmentioning
confidence: 98%
“…In addition; it greatly influences the morphology, size and density number of the main strengthening phases formed during AA [30], GP zones, β″, β′ phase, etc as well as their precipitation value contribution to the alloy [25]. As a result of the literature; Mg alloys such as Mg-RE [27], Mg-8Li-3Al-2Zn-0.5Y [28], ZK60 [31], Mg-3Sn-1Al [32], Mg-3Sn-2Zn-1Al [32] and Mg-Gd [26] were aged by AA method and aging/property correlation was investigated.…”
Section: Introductionmentioning
confidence: 99%